Konflik dan Kontestasi Fundamentalisme dan Liberalisme Para Pembela Tuhan - Badarus Syamsi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2011)
This paper tries to examine some issues considered important i.e.fīrst, the nature of fundamentalism as a manifestation of religious thought. Second, the nature of liberalism as a form of religious thought. Third, the importance of explanation about interpretation, appreciation and realization of religion which have given birth to a different mode of interpretation that does not lead to conflict.Keywords: Fundamentalism, liberalism, religion.